Staubles Bay, Trinidad - (:unkn) unknown (W.C. Ross and Co. Ltd., Trinidad, 2009)
Depicts a view of Staubles Bay, Trinidad during the colonial period
Black and White; Landscape
Keywords: Postcards; Trinidad and Tobago; Staubles Bay